Innovative and Needs-led research on β-thalassemia treatment methods - Dan, Mihai-Octavian; Gutu, Bianca-Ioana; Severin, Emilia; Tanase, Vlad-George (Frontiers in Hematology, 2023)
Beta-thalassemia is a well-known blood genetic disorder inherited in an autosomal recessive manner. Beta-thalassemia is found everywhere in the world as a rare, relatively rare, or common disease depending on the ethnic population. Affected individuals have chronic anemia associated with delayed growth, pale skin, weakness, fatigue, and more serious complications resulting in early death. Those with the severe form need frequent lifelong transfusions and depend on blood donations to survive. There is a need to deal with ineffective erythropoiesis, improve anemia, and reduce transfusion in people with beta-thalassemia. This literature mini-review highlights the healthcare needs that are not optimally met by people living with beta-thalassemia. The needs-led research can help to improve clinical outcomes through more appropriate management of the disease, increase provider satisfaction, and reduce the cost of care.